COLLECTIVE EXPRESSION OF VIOLENCE IN THE COLLECTION OF TEXTS OF THE REPUBLIC PUPPET DRAMA WORKS N. RIANTIARNO - Choirul Muklis (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2019)
The purpose of this study is describe expression of structural violence in Bagong Czech playwright, Czech Togog, Petruk and the Czech Republic Cangik by N. Riantiarno, describe expression of social violence in plays Bagong Republic, the Republic of Togog, Petruk and the Czech Republic Cangik by N. Riantiarno. describe Individual violent expression plays in Bagong Republic, the Republic of Togog, Petruk and the Czech Republic Cangik by N. Riantiarno. The expression of collective violence theory is mapped into three variations of the basic idea. In the context of the structural repression of the rights holder, the social context of the horizontal dimension of community and individual contexts both psychologically or biologically.This is a qualitative research approach. Data collection techniques used in this research is the engineering documentation, read technique, as well as the techniques noted. Description of the analytical techniques used to describe data and content analysis was used to analyze the meaning of the message and reveal the message in the data.The results of this study (1) expression of structural violence in the data source, is dominated by the behavior of government officials to launch an interest group, (2) the expression of social violence in the data source, dominated by injustice policies and perspectives, (3) the expression of violent individual in the data source, is dominated by the behavior of retention of existence and desire control of power. Keywords Violence collective and Czech Puppe